Visualising the Global Shift in Energy Demand and Supply - Isma’il, Muhammad (International Journal of Energy Economics and Policy, 2012)
The global energy demand depends on supplies from fossil fuels responsible for climate change. The supply of the fossil fuels required to meet the global energy demand depends on production from the available proved reserves of oil, coal and gas unevenly distributed around the world. On the other hand, the energy demand of a country is determined by its economic growth and population dynamics. The industrialised nations accounted for the rising demand in global primary energy. However, a global shift is underway with the developing economies being responsible for most of the increase in global energy demand. Moreover, statistics suggest that the global energy production and consumption vary spatially and temporally. This study utilised cartograms to visualise the global shift in production and consumption of fossil fuels; because of its implication on global energy security and climate change. We observed that cartograms which are rarely used in energy visualisations provide informative and intuitive picture of the global shift in energy demand and supply. Keywords: Energy consumption; Energy production; Energy security; Fossil fuels. JEL Classifications: Q4; Q41